2022
DOI: 10.1002/slct.202201502
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Antiproliferative Activity Studies of a Thiazole‐Based Compound Linked to Hydrazone Moiety

Abstract: (A new 4‐oxothiazolidin‐2‐ylidene derivative bearing hydrazone moiety was synthesized via Michael addition between the reaction of 4‐(4‐nitrophenyl)‐3‐thiosemicarbazide and dimethyl acetylenedicarboxylate (DMAD). The structure of synthesized compound was elucidated using various spectral techniques such as FTIR, UV‐spec, 1H NMR and 13C NMR. The structure of the related compound was confirmed by single‐crystal X‐ray analysis. Antiproliferative activity of the synthesized compound was evaluated in two human canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…1). A variety of thiazole derivatives are also used as target products as well as synthetic intermediates (Maharramov et al, 2011a;Kekec ¸muhammed et al, 2022).…”
Section: Chemical Contextmentioning
confidence: 99%
“…1). A variety of thiazole derivatives are also used as target products as well as synthetic intermediates (Maharramov et al, 2011a;Kekec ¸muhammed et al, 2022).…”
Section: Chemical Contextmentioning
confidence: 99%
“…2), [11][12][13] in addition to activities against other diseases such as bacterial and fungal infections. [14][15][16][17] The bioactivity of compounds containing a hydrazone moiety is conjectured from its ability to form hydrogen bonds with molecular targets, making the compounds with this scaffold easily bind to numerous receptors and enzymes. 18 It is seen from the literature that Dandawate et al reported significant anti-breast cancer activities of hydrazone derivatives V by inhibiting NF-kB protein expression via interaction by hydrogen bonds of the hydrazone moiety and amino acid residue in p50-subunits.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 One of the principal strategies for drug discovery of new drug candidates is to amalgamate two or more pharmacophoric moieties in a single molecule to achieve the synergistic effect or obtain anticancer agents via a novel mechanism of action. In light of the afore-mentioned facts and continuation of our previous studies on identifying new antiproliferative activities, 16,[23][24][25][26] hybrid compounds containing a 1,2,4-triazole ring and a hydrazone moiety were synthesized by employing an iodine mediated reaction in an attempt to get new effective anticancer molecules with increased potency (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…[14] Also, Zhang et al reported some imidazole derivatives (3) as anti-prostate cancer agents which exhibited good anticancer activity with selectivity on health cell lines as good as clinical administered drugs. [15] Additionally, hydrazone functionality has been reported to exhibit remarkable anticancer activity, [16,17] in addition to activities against other diseases such as bacterial and fungal infections. [18,19] The bioactivity based on hydrazone moiety was hypothesized to be due to the hydrazone's capacity to process additional reactions with a class of nucleophiles such as thiol À SH and the amino À NH 2 and form hydrogen bonds with molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hydrazone functionality has been reported to exhibit remarkable anticancer activity, [16,17] in addition to activities against other diseases such as bacterial and fungal infections [18,19] . The bioactivity based on hydrazone moiety was hypothesized to be due to the hydrazone's capacity to process additional reactions with a class of nucleophiles such as thiol −SH and the amino −NH 2 and form hydrogen bonds with molecular targets [20] .…”
Section: Introductionmentioning
confidence: 99%